Research with female athletes: Choosing the best tools for the job - McGawley, K.; Taylor, M. Y.; Brown, N.; Harrison, S. E.; Bruinvels, G.; Badenhorst, C. E. (International Journal of Sports Physiology and Performance, 2025)
An increasing number of sport and exercise-science studies include female athletes, which strengthens our evidence base for translating knowledge into applied practice. Between 2019 and 2022 the proportion of IJSPP original investigations and brief reports including women increased from 19% to 28%, and studies that were performed exclusively on female athletes, from 4% to 12%. This collective research response is aligned with various calls to action from researchers in sport and exercise science, applied practitioners, and athletes to enhance our understanding of how best to support girls and women in sport.